Psychological characteristics of preventing deviant behavior among minors - Rakhmonova Dildora Zayniddinovna (Psychohealth: Scientific Journal of Psychology and Mental Health, 2025)
Purpose: This study aims to analyze the psychological characteristics underlying the prevention of deviant behavior among minors. It seeks to identify the emotional, cognitive, and social factors influencing behavioral deviation and to propose effective preventive strategies grounded in psychological development and social adaptation. Methodology: A mixed-method design combining quantitative and qualitative approaches was used. Data were collected through psychological assessments, structured interviews, and behavioral observations. The study involved minors exhibiting risk factors for deviance and examined variables such as family dynamics, emotional intelligence, empathy, and self-regulation. Preventive interventions included counseling, group training, and emotional education sessions. Results: Findings revealed that emotional instability, poor self-regulation, and dysfunctional family environments were primary predictors of deviant behavior. Participation in psychological training led to significant improvements in empathy, emotional control, and cooperative behavior. The results demonstrated that early preventive interventions focusing on emotional intelligence and family engagement effectively reduce antisocial tendencies. Conclusion: Deviant behavior among minors originates primarily from emotional and psychological disbalance. Prevention must therefore emphasize empathy, self-control, and family-based support as core components of psychological education. Limitations: The study’s sample was regionally limited, and cultural factors were not deeply examined, restricting generalization. Contribution: This research offers a comprehensive framework for integrating psychological prevention into education systems, highlighting the importance of emotional intelligence, family involvement, and school-based interventions in promoting moral and social development among minors.